Sphenoid mucopyocele causing bilateral sixth nerve palsy. Issue 1 (21st January 2022) - Kelly, Mairead; Chang, Liisa; Patel, Parag; Weller, Alexander; Advani, Rajeev; Lakhani, Raj
Abstract: Sphenoid mucoceles, although rare, should be considered in patients with headache, visual disorders and eye paralysis. Due to close relationships with the orbit and neuromeningeal structures, early recognition is vital. We report the case of a patient who presented with bilateral abducens nerve palsies. At surgery, she was found to have a mucopyocele; this was drained and she required prolonged intravenous antibiotic therapy due to ongoing symptoms and persistent dural enhancement on imaging. A lesion of sufficient size in the clival area has the potential to cause bilateral abducens nerve palsies, though we believe this is the first time it has been described in relation to a sphenoid mucocele. Imaging plays a crucial role in diagnosis, and prompt surgical intervention is essential to avoid serious and permanent complications. The multi-disciplinary team approach is vital—these cases requiring input from ophthalmology, ear nose and throat, microbiology, radiology, neurology and neurosurgery.